2006
DOI: 10.1021/jo061571y
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Enzymatic Reductions of Sterically Bulky Aryl Alkyl Ketones Catalyzed by a NADPH-Dependent Carbonyl Reductase

Abstract: The enantioselective reductions of aryl alkyl ketones, ArC(O)R, with a diverse number of alkyl groups have been achieved with an isolated carbonyl reductase from Sporobolomyces salmonicolor. Of special interest is the observation that ketones with sterically bulky alkyl groups could be reduced to the corresponding alcohols in excellent optical purity. An unusual alkyl chain-induced enantiopreference reversal was observed but was shown to be consistent with the enzyme-substrate docking calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…This unique substrate-binding domain suggests that SSCR might possess an unusual substrate specificity and stereoselectivity. Indeed, SSCR shows an unusually broad substrate range including aliphatic, aromatic ketones, αand β-ketoesters, and sterically bulky aryl alkyl ketones and diaryl ketones [26,27].…”
Section: Carbonyl Reductase From Sscrmentioning
confidence: 99%
“…This unique substrate-binding domain suggests that SSCR might possess an unusual substrate specificity and stereoselectivity. Indeed, SSCR shows an unusually broad substrate range including aliphatic, aromatic ketones, αand β-ketoesters, and sterically bulky aryl alkyl ketones and diaryl ketones [26,27].…”
Section: Carbonyl Reductase From Sscrmentioning
confidence: 99%
“…[1] Biocatalysts have been demonstrated to be highly enantioselective in the reduction of a wide range of ketones including some bulky ones. [27][28][29] Enzymatic reduction offers a potentially complementary way of achieving highly enantioselective reduction of diaryl ketones that are difficult with chemical catalysts. [30] In this context, a few reports dealing with the biocatalytic reduction of diaryl ketones have appeared.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, it has been found that a carbonyl reductase from red yeast Sporobolomyces salmonicolor AKU4429 (SSCR) catalyzed the highly enantioselective reduction of a wide range of ketones including 2,2-dimethylpropiophenone, 1-phenyl-1-pentanone and cyclopropylA C H T U N G T R E N N U N G (phenyl)methanone, showing that it is a useful biocatalyst for the reduction of sterically bulky ketones. [28,39] We envisioned that the carbonyl reductase SSCR might also take sterically bulky diaryl ketones as substrates. Herein we report that a variety of diaryl ketones were enantioselectively reduced by this carbonyl reductase and its mutant enzyme Q245P.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Interestingly, when the alkyl group becomes branched (221gÀi, entries 7À8) the (R)-enantioselectivity comes back and in very high ee values. 188 The corresponding favored binding modes could be predicted by means of an automated docking protocol which makes use of the interaction energy of the substrates in the active site of the enzyme as scoring function. 189 Bisaryl ketones are an example of bulkyÀbulky ketones, the reduction of which affords optically active diarylmethanols, important chiral synthons.…”
Section: Scheme 40mentioning
confidence: 99%